'Achieving a profitable low carbon transition: Learning from an entrepreneurial approach' - Conley, Daniel; Hargroves, Charlie; Lambert, Martin; Newman, Peter (2017)
The cities of the world are growing at a rapid pace and as hubs of economic development, production, and consumption, cities must effectively navigate lowcarbon transitions if the world is to mitigate the effects of climate change within the internationally agreed timeframe. Much of the technology needed to enable this low carbon transition has existed for decades, however progress has remained slow due to complex challenges within cities that cannot be overcome with traditional approaches. This paper will present the case that approaches taken by entrepreneurs, who operate in fast-paced and uncertain conditions, could be invaluable in informing low-carbon energy transitions at a city, national and regional level. Some schools of thought suggest that the capacity and responsibility to address climate change lies with governments through policy, while others suggest individual entrepreneurs are key to accelerating climate efforts, with a tendency to rely on such individuals rather than learning from and applying their approach. This paper presents a middle ground where policy makers, researchers, business, and civil organisations seek to learn from an entrepreneurial approach in order to accelerate the worlds low carbon transition. This paper presents an overview of key entrepreneurial approaches suited to accelerating the low carbon transition with a focus on urban infrastructure. Guidance will also be provided on how such an approach can be applied at a macro-level while also strategically supporting emerging bottom-up innovations occurring at the micro-level which play an important role in transitioning systems.